MENINGKATKAN KUALITAS PENDIDIKAN DASAR DENGAN PENDEKATAN FOKUS PADA PELANGGAN (STUDI KASUS SD NEGERI DI KOTA SAMARINDA) - wahyudi nafarin, wahyu; Desi Lastsari, Sotinsia; Riza Maulida, Rizki Riza Maulida; Azinil, Azainil; Komariyah, Laili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The quality of primary education is a fundamental element in the development of qualified human resources. In an effort to improve the quality of education, the application of quality management principles, including the principle of customer focus, becomes crucial. Customer satisfaction, which includes students, parents, the community, and other stakeholders, is a key indicator in assessing the success of an educational institution. Identifying the needs and expectations of education service users is essential in providing adequate and satisfactory services. This study highlights the importance of customer satisfaction in the context of primary education as a benchmark for the success of educational delivery. Effective communication between teachers and students, as well as responsiveness to feedback and inquiries from customers, plays an integral role in improving educational service quality. By understanding and analyzing customer satisfaction, educational institutions can continuously innovate and enhance the quality of the services they provide.